A taxonomic revision of the Pourthiaea villosa complex (Rosaceae) - Liu, Binbin; Hong, Deyuan (Phytotaxa, 2016)
The taxonomy of the Pourthiaea villosa complex, distributed in E Asia, is extremely controversial. The lack of proper analysis and evaluation of the characters used previously may have caused these controversies among taxonomists. The present study is the first comprehensive taxonomic revision of this complex. We have conducted extensive field observations, population sampling, examination of a large number of specimens and subsequent statistical analysis. All morphological characters used in previous taxonomic treatments were analyzed one by one. They include length, breadth, basal angle, and apex of leaf blade, length of petiole, length of pedicel, number of flowers, and density of indumentum on leaves, petiole, pedicel, hypanthium, and branchlets. We found that these characters were extremely variable both within and between populations of this complex. Such variations are continuous or with no statistical support, and there is no correlation between the different characters. Therefore, the characters used in this complex are of little value for species delimitation. As a result of our study, only one species, P. villosa, is recognized, without subdivision. Fourteen names are reduced as new synonyms of P. villosa. In addition, P. villosa is designated as the type of Pourthiaea and 10 lectotypes are designated.